A graphene oxide / carbon nanotube-nano nickel electrode and its preparation method and application
By using graphene oxide/carbon nanotube-nano nickel composite materials, electrode preparation is solved by using 3D printing and high-temperature calcination technology, the problems of low catalytic efficiency and difficult industrialization under low overpotential in the existing technology are solved, and high-efficiency catalytic water is achieved The effect of decomposition and easy industrial production.
Patent Information
- Application Number
- CN202211322783.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-10-27
AI Technical Summary
The prior art is difficult to efficiently catalyze water decomposition under low overpotentials, and the industrialization of 3D printed electrodes is difficult, which has problems such as high energy consumption and high environmental governance costs.
The electrodes were prepared by 3D printing technology and combined with high-temperature calcination process to form electrodes with macroscopic ordered grid structure.
It realizes efficient catalytic water decomposition at low overpotentials, the electrodes exhibit good corrosion resistance and cycle stability, and the process is easy to industrialize and mass production.
Smart Images

Figure CN115732656B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogen production electrodes and relates to a nickel electrode, in particular to a graphene oxide / carbon nanotube-nano nickel electrode and a preparation method and application thereof. Background Art
[0002] The combustion calorific value of hydrogen is 4.5 times that of coke, and the chemical energy conversion product is clean and pollution-free water, which can realize resource recycling. The hydrogen element on the earth mainly exists in the form of compounds. Through appropriate utilization, hydrogen energy is expected to become the ultimate form of future energy development.
[0003] With the rapid growth of the world economy and population, the demand for energy is increasing day by day. Traditional fossil energy is predicted to be exhausted within 150 years, and the development of renewable and sustainable hydrogen energy is imminent. By combining with clean electricity such as photovoltaics and wind power, water electrolysis to produce hydrogen is the main way to achieve the production of "green hydrogen" with true zero carbon dioxide emissions. For example, solid oxide electrolysis has high conversion efficiency, but it is still in the laboratory stage; proton exchange membrane electrolysis is flexible in operation and small in equipment size, but it requires the use of rare metals such as platinum and iridium, which is costly and has large supply chain limitations.
[0004] Alkaline electrolysis technology is highly mature and only requires cheap metal nickel as a catalyst to achieve stable and efficient water-hydrogen conversion. At present, domestic industrial water electrolysis mostly uses nickel mesh or Raney nickel electrodes, and its performance index is 300mA / cm 2 @1.84V. The foreign technology is more mature, and the industrial current density index of foreign nickel-based alloy electrodes has reached 400mA / cm 2 @1.8V, there is still a big gap between the domestic and foreign water electrolysis hydrogen production industries. There have been reports of 3D printing technology used to prepare nickel-based alloy electrodes abroad. 3D printing technology can achieve macro-ordered regulation of the electrode structure, thereby promoting gas overflow during the electrolysis process and exposing more active sites. The performance of 3D printed nickel-based alloy electrodes in the anode oxygen evolution reaction of water electrolysis is improved compared to industrial nickel-based alloy electrodes, but there is a problem that the preparation is difficult to industrialize. Jun Ding et al. prepared alloy composite electrodes by laser melting printing, but the energy consumption of this strategy is too high and is not suitable for large-scale production. Yat Li et al. prepared nickel-based electrodes by ink direct writing printing, but the use of organic phase ink system increased the cost of environmental governance.
[0005] In response to the above problems, we urgently need to develop an easily industrialized 3D-printed electrode that can efficiently catalyze water decomposition at low overpotential, so that it can be used in alkaline water electrolysis. Summary of the invention
[0006] In view of the defects of the above-mentioned prior art, the present invention provides a method for preparing a graphene oxide / carbon nanotube-nano nickel electrode.
[0007] To achieve the above object, the present invention provides a method for preparing a graphene oxide / carbon nanotube-nano nickel electrode, comprising the following steps:
[0008] (a) dispersing graphene oxide and carbon nanotubes in deionized water to obtain a graphene oxide / carbon nanotube mixed solution;
[0009] (b) swelling the acrylic cross-linked resin and the polyoxyethylene polypropylene triblock polymer in deionized water to obtain an acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel;
[0010] (c) adding nano nickel powder to the graphene oxide / carbon nanotube mixed solution and stirring evenly; then adding the acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel and mixing evenly to obtain graphene oxide / carbon nanotube-nano nickel composite ink;
[0011] (d) loading the graphene oxide / carbon nanotube-nano nickel composite ink into a 3D printer, setting the 3D printer parameters, and performing 3D printing on a glass sheet as a substrate to obtain a graphene oxide / carbon nanotube-nano nickel composite hydrogel;
[0012] (e) freeze-drying the graphene oxide / carbon nanotube-nano-nickel composite hydrogel to obtain a graphene oxide / carbon nanotube-nano-nickel composite aerogel; and calcining the graphene oxide / carbon nanotube-nano-nickel composite aerogel at a high temperature under an inert gas to obtain a graphene oxide / carbon nanotube-nano-nickel electrode.
[0013] Optimally, step (a) comprises:
[0014] (a1) mixing graphene oxide and deionized water, and ultrasonicating and stirring to obtain a graphene oxide solution;
[0015] (a2) mixing the carbon nanotubes with a mixed acid, stirring and reacting under heating conditions; then washing with deionized water and filtering to obtain a concentrated carbon nanotube solution, and calibrating its solid content; the mixed acid is a mixture of concentrated nitric acid and concentrated sulfuric acid;
[0016] (a3) ultrasonically mixing the graphene oxide solution and the concentrated carbon nanotube solution to obtain the graphene oxide / carbon nanotube mixed solution.
[0017] Furthermore, the concentration of the graphene oxide solution is 10-30 mg / mL, the concentration of the concentrated carbon nanotube solution is 150-200 mg / mL, the feeding ratio of the carbon nanotubes, concentrated nitric acid and concentrated sulfuric acid is 1 g: 10-20 mL: 25-50 mL, and the feeding volume ratio of the graphene oxide solution to the concentrated carbon nanotube solution is 8-15:1.
[0018] Optimally, step (b) comprises:
[0019] (b1) mixing an acrylic acid cross-linked resin and deionized water, and allowing the mixture to stand and swell to obtain an acrylic acid cross-linked resin gel;
[0020] (b2) mixing the polyoxyethylene polypropylene triblock polymer and deionized water, and allowing the mixture to swell to obtain a polyoxyethylene polypropylene triblock polymer gel;
[0021] (b3) mixing the acrylic cross-linked resin gel and the polyoxyethylene polypropylene triblock polymer gel to obtain an acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel.
[0022] Furthermore, the concentration of the acrylic cross-linked resin is 15-25 mg / mL, the concentration of the polyoxyethylene polypropylene triblock polymer is 5-15 mg / mL, and the feed volume ratio of the acrylic cross-linked resin gel to the polyoxyethylene polypropylene triblock polymer gel is 1:0.8-1.2.
[0023] Optimally, in step (c), the mass ratio of the nano nickel powder, the graphene oxide / carbon nanotube mixed solution and the acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel is 1500-2000:200-400:100-150.
[0024] Optimally, in step (e), the high temperature calcination is carried out by heating the material to 500-900° C. at a rate of 1-10° C. / min in a tubular furnace.
[0025] Optimally, in step (d), the graphene oxide / carbon nanotube-nano nickel composite ink is placed in a 3D printer syringe, and a printing needle compatible with the syringe is used; the diameter of the printing needle is 100-2000 μm, and the distance between the free end of the printing needle and the substrate is 0.70 to 0.8 times the diameter of the printing needle; the 3D printer parameters include: the air pressure is 90 to 400 kPa, and the movement speed of the robotic arm is 1 to 30 mm / s.
[0026] Another object of the present invention is to provide a graphene oxide / carbon nanotube-nano nickel electrode, which is prepared by any of the above-mentioned methods.
[0027] Another object of the present invention is to provide an application of a graphene oxide / carbon nanotube-nano nickel electrode for electrolyzing water under alkaline conditions.
[0028] Due to the application of the above technical scheme, the present invention has the following advantages compared with the prior art: the preparation method of the graphene oxide / carbon nanotube-nano nickel electrode of the present invention, by mixing the graphene oxide / carbon nanotube mixed solution and the acrylic acid cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel to obtain a composite ink, and then performing 3D printing and calcination, can obtain an electrode with the advantages of low alkaline water electrolysis driving potential, good catalytic performance, corrosion resistance, good cyclic application stability, etc., and the preparation process is easy to industrialize and convert on a large scale, and the macroscopic ordered lattice structure effectively promotes the transmission of substances related to the catalytic reaction and the escape of gas bubbles of water electrolysis products, and has broad application prospects in electrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The preparation process and structural characterization of the 3D printed graphene oxide / carbon nanotube-nano nickel composite electrode of the present invention: (a) optical image of Example 1; (bd) SEM characterization images of Example 1 at different magnifications; (e) XRD spectrum of Example 1; (f) XPS Ni 2p spectrum of Example 1; (g) high-resolution TEM characterization image of Example 1; (h) element mapping image of Example 1;
[0030] Figure 2 The alkaline water electrolysis test performance of the graphene oxide / carbon nanotube-nano nickel composite electrode is as follows: (a) linear voltammogram of the hydrogen evolution half reaction of Example 1; (b) linear voltammogram of the oxygen evolution half reaction of Example 1; (c) linear voltammogram of the overall water splitting of Example 1; (d) Nengquist impedance diagram of the hydrogen evolution half reaction of Example 1; (e) Nengquist impedance diagram of the oxygen evolution half reaction of Example 1; (f) linear voltammogram of the overall water splitting of Example 1 under light heating conditions;
[0031] Figure 3 It is a comparison diagram of the alkaline overall water splitting performance of the graphene oxide / carbon nanotube-nano nickel composite electrode (Example 1) and other nickel foam substrate modified material electrodes reported in recent years;
[0032] Figure 4The alkaline water electrolysis test performance and structural characterization of the graphene oxide / carbon nanotube-nano nickel composite electrode after trace Pt modification: (a) Linear voltammetric curve of the hydrogen evolution half reaction after trace Pt modification in Example 1; (b) Tafel slope diagram of the hydrogen evolution half reaction after trace Pt modification in Example 1; (c) ICP concentration diagram of the Pt content in the modified electrolyte before and after trace Pt modification in Example 1; (d) SEM element mapping diagram of trace Pt modification in Example 1;
[0033] Figure 5 The alkaline water electrolysis test performance and structural characterization of the graphene oxide / carbon nanotube-nano nickel composite electrode after NiFeOOH modification: (a) Linear voltammetry curve of the oxygen evolution half reaction after NiFeOOH modification in Example 1; (b) Linear voltammetry curve of the overall water splitting after NiFeOOH modification in Example 1; (c) Linear voltammetry curve of the overall water splitting under light heating conditions after NiFeOOH modification in Example 1; (d) SEM characterization image of Example 1 after NiFeOOH modification; (e) XPS Ni 2p spectrum of Example 1 after NiFeOOH modification; (f) XPS Fe 2p spectrum of Example 1 after NiFeOOH modification; (g) SEM element mapping image of Example 1 after NiFeOOH modification. DETAILED DESCRIPTION
[0034] The preparation method of the graphene oxide / carbon nanotube-nano nickel electrode of the present invention comprises the following steps: (a) dispersing graphene oxide and carbon nanotubes in deionized water to obtain a graphene oxide / carbon nanotube mixed solution; (b) swelling an acrylic acid crosslinking resin and a polyoxyethylene polypropylene triblock polymer in deionized water to obtain an acrylic acid crosslinking resin / polyoxyethylene polypropylene triblock polymer mixed gel; (c) adding nano nickel powder to the graphene oxide / carbon nanotube mixed solution and stirring evenly; and then adding the acrylic acid crosslinking resin / polyoxyethylene polypropylene triblock polymer mixed gel and mixing evenly to obtain a (d) loading the graphene oxide / carbon nanotube-nano nickel composite ink into a 3D printer, setting the 3D printer parameters, and performing 3D printing on a glass sheet as a substrate to obtain a graphene oxide / carbon nanotube-nano nickel composite hydrogel; (e) freeze-drying the graphene oxide / carbon nanotube-nano nickel composite hydrogel to obtain a graphene oxide / carbon nanotube-nano nickel composite aerogel; and calcining the graphene oxide / carbon nanotube-nano nickel composite aerogel at a high temperature under an inert gas to obtain a graphene oxide / carbon nanotube-nano nickel electrode. By mixing a graphene oxide / carbon nanotube mixed solution and an acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel to obtain a composite ink, and then performing 3D printing and calcination, an electrode with the advantages of low alkaline water electrolysis driving potential, good catalytic performance, corrosion resistance, and good cyclic application stability can be obtained. The preparation process is easy to industrialize and convert on a large scale, and the macroscopic ordered lattice structure effectively promotes the transmission of substances related to the catalytic reaction and the escape of gas bubbles of water electrolysis products, which has broad application prospects in electrocatalysis.
[0035] Step (a) preferably comprises: (a1) mixing graphene oxide (usually commercially available) and deionized water, ultrasonicating and stirring (e.g., ultrasonicating for 0.5 to 2 hours and then stirring for 2 to 5 hours) to obtain a graphene oxide solution; (a2) mixing carbon nanotubes (usually commercially available) with mixed acid, stirring and reacting under heating conditions (e.g., stirring at 80 to 95° C. for 1 to 2 hours); then washing with deionized water and filtering to obtain a concentrated carbon nanotube solution, and calibrating its solid content; the mixed acid is a mixture of concentrated nitric acid and concentrated sulfuric acid; (a3) The graphene oxide solution is ultrasonically mixed with the concentrated carbon nanotube solution (ultrasonic time is 3 to 8 minutes) to obtain the graphene oxide / carbon nanotube mixed solution; specifically, the concentration of the graphene oxide solution is 10 to 30 mg / mL, and the concentration of the concentrated carbon nanotube solution is 150 to 200 mg / mL, that is, the concentration of graphene oxide in the graphene oxide solution is 10 to 30 mg / mL, and the concentration of carbon nanotubes in the concentrated carbon nanotube solution is 150 to 200 mg / mL. The feeding ratio of the carbon nanotubes, concentrated nitric acid and concentrated sulfuric acid is 1g: 10 to 20 mL: 25 to 50 mL, and the feeding volume ratio of the graphene oxide solution to the concentrated carbon nanotube solution is 8 to 15: 1.
[0036] Step (b) preferably includes: (b1) mixing an acrylic cross-linked resin and deionized water, and allowing to swell (generally for 3 to 5 hours) to obtain an acrylic cross-linked resin gel; (b2) mixing a polyoxyethylene polypropylene triblock polymer and deionized water, and allowing to swell (generally for 3 to 5 hours) to obtain a polyoxyethylene polypropylene triblock polymer gel; (b3) mixing the acrylic cross-linked resin gel and the polyoxyethylene polypropylene triblock polymer gel to obtain an acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel. The concentration of the acrylic cross-linked resin is 15 to 25 mg / mL (i.e., the content of the acrylic cross-linked resin in the acrylic cross-linked resin gel is 15 to 25 mg / mL), the concentration of the polyoxyethylene polypropylene triblock polymer is 5 to 15 mg / mL (i.e., the content of the polyoxyethylene polypropylene triblock polymer in the polyoxyethylene polypropylene triblock polymer gel is 5 to 15 mg / mL), and the feed volume ratio of the acrylic cross-linked resin gel to the polyoxyethylene polypropylene triblock polymer gel is 1:0.8 to 1.2, preferably 1:1.
[0037] In step (c), the mass ratio of the nano nickel powder, the graphene oxide / carbon nanotube mixed solution and the acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel is preferably 1500-2000:200-400:100-150, and the optimal ratio is 1800:107:300. In step (d), preferably, the graphene oxide / carbon nanotube-nano nickel composite ink is placed in a 3D printer syringe, and a printing needle compatible with the syringe is used; the diameter of the printing needle is 100-2000 μm, and the distance between the free end of the printing needle and the substrate is 0.70-0.8 times the diameter of the printing needle; the 3D printer parameters include: air pressure of 90-400 kPa, and the moving speed of the robot arm is 1-30 mm / s (this parameter range has little effect on the performance of the product). In step (e), the high temperature calcination is preferably carried out by heating the material to 500 to 900° C. at a rate of 1 to 10° C. / min in a tubular furnace.
[0038] The graphene oxide / carbon nanotube-nano nickel electrode of the present invention is prepared by any of the above methods; the graphene oxide / carbon nanotube-nano nickel electrode can be used for electrolyzing water under alkaline conditions.
[0039] The preferred embodiments of the present invention are described in detail below.
[0040] Example 1
[0041] This embodiment provides a graphene oxide / carbon nanotube-nano nickel electrode, comprising the following steps:
[0042] (a) Commercially available graphene oxide and deionized water were mixed, ultrasonicated for 1 hour and stirred for 3 hours to obtain a uniform graphene oxide solution (the graphene oxide solution concentration was 20 mg / mL); commercially available carbon nanotubes were mixed with concentrated nitric acid and concentrated sulfuric acid in a ratio of 1 g:11 mL:33 mL, stirred at 90° C. for 1.5 hours, washed with deionized water and filtered to obtain a concentrated carbon nanotube solution, the solid content of which was calibrated to be 188 mg / mL (i.e., the solid content of the concentrated carbon nanotube solution); the graphene oxide solution and the concentrated carbon nanotube solution were mixed at a feed volume ratio of 10:1, ultrasonicated for 5 minutes, and a graphene oxide / carbon nanotube mixed solution (concentration was 35 mg / mL) was obtained;
[0043] (b) mixing an acrylic cross-linked resin and deionized water, standing for 4 hours for swelling, and obtaining an acrylic cross-linked resin gel (concentration of 20 mg / mL); mixing a polyoxyethylene polypropylene triblock polymer and deionized water, standing for 4 hours for swelling, and obtaining a polyoxyethylene polypropylene triblock polymer gel (concentration of 10 mg / mL); mixing the acrylic cross-linked resin gel and the polyoxyethylene polypropylene triblock polymer gel in a feed volume ratio of 1:1, and obtaining an acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel (concentration of 15 mg / mL);
[0044] (c) adding 1.8 g of nano-nickel powder to 8.57 mL of graphene oxide / carbon nanotube mixed solution (35 mg / mL), stirring for 30 min to evenly disperse the nano-nickel powder, then adding 7.13 mL of acrylic resin / polyoxyethylene polypropylene triblock polymer mixed gel (15 mg / mL), and mixing evenly to obtain graphene oxide / carbon nanotube-nano-nickel composite hydrogel ink;
[0045] (d) placing the above-mentioned graphene oxide / carbon nanotube-nano nickel composite ink into a 10 mL syringe of a 3D printer (the printing needle of the 3D printer is adapted to the syringe, the diameter of the printing needle is 100 μm, and the distance between the free end of the printing needle and the substrate is 0.75 times the diameter of the printing needle), and setting the 3D printer parameters (pre-setting the movement program of the 3D printer mechanical arm, selecting the air pressure to be 100 kPa, and the movement speed of the mechanical arm to be 10 mm / s), and performing 3D printing on a glass sheet as a substrate to obtain a graphene oxide / carbon nanotube-nano nickel composite hydrogel;
[0046] (e) The graphene oxide / carbon nanotube-nano-nickel composite hydrogel was freeze-dried for 10 h to obtain a graphene oxide / carbon nanotube-nano-nickel composite aerogel; the graphene oxide / carbon nanotube-nano-nickel composite aerogel was calcined at a high temperature (heating to 800° C. in a tubular furnace at a heating rate of 5° C. / min for 2 h) under a nitrogen atmosphere to obtain a graphene oxide / carbon nanotube-nano-nickel composite electrode. Some of the properties of the electrode are shown in Figure 1 shown.
[0047] It can be seen that the graphene oxide / carbon nanotube-nano nickel electrode prepared in this embodiment has a high alkaline water electrolysis performance, which can be obtained from the current density value ( Figure 2 a- Figure 2 f) shows that the current density under industrial conditions is as high as 756 mA cm -2 The obtained 3D printed composite electrode has low contact resistance and fast charge transfer. Figure 2 d and Figure 2e can be seen. Compared with the reported nickel foam substrate electrode, the 3D printed composite electrode obtained in this embodiment has great advantages. At the same time, modification on the obtained composite electrode can further improve the water electrolysis performance ( Figure 3-Figure 5 ). The macroscopic ordered grid structure effectively promotes the transport of substances related to the catalytic reaction and the escape of gases, and has broad application prospects in electrocatalysis.
[0048] Example 2
[0049] This embodiment provides a graphene oxide / carbon nanotube-nano nickel electrode, which is basically the same as Example 1, except that: in step (c), 4.53 mL of acrylic resin / polyoxyethylene polypropylene triblock polymer mixed gel is added.
[0050] Example 3
[0051] This embodiment provides a graphene oxide / carbon nanotube-nano nickel electrode, which is basically the same as Example 1, except that in step (c), 12.3 mL of acrylic resin / polyoxyethylene polypropylene triblock polymer mixed gel is added.
[0052] Example 4
[0053] This embodiment provides a graphene oxide / carbon nanotube-nano nickel electrode, which is basically the same as Example 1, except that: in step (c), 2.7 g of nano nickel powder is added.
[0054] Example 5
[0055] This embodiment provides a graphene oxide / carbon nanotube-nano nickel electrode, which is basically the same as Example 1, except that in step (c), 3.6 g of nano nickel powder is added.
[0056] Comparative Example 1
[0057] This example provides a graphene oxide / carbon nanotube electrode, which is basically the same as Example 1, except that in step (c), no nano nickel powder is added.
[0058] Comparative Example 2
[0059] This embodiment provides a graphene oxide / carbon nanotube-nano nickel electrode, which is basically the same as Example 1, except that: in step (c), 0.9 g of nano nickel powder is added.
[0060] Comparative Example 3
[0061] This example provides a graphene oxide / carbon nanotube-nano nickel electrode, which is basically the same as Example 1, except that: in step (c), 5.6 g of nano nickel powder (excess nickel powder) is added.
[0062] Comparative Example 4
[0063] This example provides a carbon nanotube-nano nickel electrode, which is basically the same as Example 1, except that: in step (a), graphene oxide is not added.
[0064] Comparative Example 5
[0065] This example provides a graphene oxide-nano nickel electrode, which is basically the same as Example 1, except that: in step (a), no carbon nanotubes are added.
[0066] Comparative Example 6
[0067] This embodiment provides a graphene oxide / carbon nanotube-nano nickel electrode, which is basically the same as Example 1, except that in step (c), 2.68 mL of graphene oxide / carbon nanotube mixed solution is added.
[0068] The above embodiments and comparative examples were tested as follows, and the specific experimental conditions and methods are as follows (i.e., alkaline electrolyzed water performance test):
[0069] All electrochemical measurements were performed on a CHI-660E electrochemical station (Shanghai Chenhua) connected to a CHI1140C high-power potentiostat / galvanostat: the electrolyte was 1 M KOH aqueous solution, and the area of the electrodes immersed in the electrolyte was 0.25 cm 2 .
[0070] The standard three-electrode system for measuring the half-reaction of water electrolysis is as follows: the electrodes prepared in the above embodiments and comparative examples are directly used as working electrodes, and the silver / silver chloride electrode (1M KOH) is used as the reference electrode. During the HER test, the graphite rod is used as the counter electrode; during the OER test, the platinum sheet is used as the counter electrode. The overpotential (η) of OER is calculated by the equation η = Erhe-1.23V. Before the linear sweep voltammetry test, the overpotential (η) of OER is calculated by 50mV·s -1 Cyclic voltammetry was performed for 12 cycles at a scan rate of 5 mV·s -1 The LSV curve was recorded at a scan rate of 1000 nm and the IR compensation rate was 85%. The η curve was plotted using log|j| and the Tafel slope was calculated. -2 Electrochemical impedance spectroscopy was obtained at a voltage of 1.04 V and a frequency range of 100 kHz to 0.1 Hz.
[0071] The overall water splitting experiment is basically the same as the half-reaction experiment, except that: the electrodes prepared in the above embodiments and comparative examples are used as anode and cathode, and are carried out in a two-electrode system (unless otherwise specified, all reported potentials are calibrated to a reversible hydrogen electrode according to the equation: Erhe=EAg / AgCl+0.205+0.059×pH(V), and the results are shown in Table 1.
[0072] Table 1 Electrochemical performance of electrodes in Examples 1-5 and Comparative Examples 1-6
[0073]
[0074] In order to improve the current density of the whole water splitting, the above graphene oxide / carbon nanotube-nano nickel electrode is also modified during application. Taking the graphene oxide / carbon nanotube-nano nickel electrode (referred to as 3DP Ni) in Example 1 as an example, the specific modification method is as follows (test results are shown in Table 2):
[0075] (1) Pt modification
[0076] The obtained graphene oxide / carbon nanotube-nano nickel electrode was electrochemically deposited in a three-electrode system, and the deposited electrode was referred to as 3DP Ni-Pt. The working electrode was graphene oxide / carbon nanotube-nano nickel electrode, the counter electrode was a graphite rod electrode, and the reference electrode was a saturated calomel electrode (SCE); the electrolyte was 0.013mM H2PtCl6+1M KOH; CV cyclic deposition, the voltage was -1.07~-1.57V vs SCE, and the deposition time was 300 cycles.
[0077] (2) Ni / NiO modification
[0078] The obtained graphene oxide / carbon nanotube-nano nickel electrode was electrochemically deposited in a three-electrode system, and the electrode after deposition is referred to as 3DP Ni-Ni / NiO. The working electrode is a graphene oxide / carbon nanotube-nano nickel electrode, the counter electrode is a graphite rod electrode, and the reference electrode is a saturated calomel reference electrode (SCE); the electrolyte is 0.02M Ni(CH3COO)2; constant voltage deposition, the voltage is -1~-3V vs SCE, and the deposition time is 200s.
[0079] (3) NiFeOOH modification
[0080] The obtained graphene oxide / carbon nanotube-nano nickel electrode was electrochemically deposited in a three-electrode system, and the deposited electrode was referred to as 3DP Ni-NiFeOOH. The working electrode was graphene oxide / carbon nanotube-nano nickel electrode, the counter electrode was a graphite rod electrode, and the reference electrode was a saturated calomel electrode; the electrolyte was 0.135M NiCl6+0.165M FeCl2; constant voltage deposition, the voltage was -1~1.8V vs SCE, and the deposition time was 180s.
[0081] Table 2 Electrochemical performance of the modified electrode of Example 1
[0082]
[0083] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a graphene oxide / carbon nanotube-nano nickel electrode, characterized in that: The following steps are involved: (a) dispersing graphene oxide and carbon nanotubes in deionized water to obtain a graphene oxide / carbon nanotube mixed solution; (b) swelling the acrylic cross-linked resin and the polyoxyethylene polypropylene triblock polymer in deionized water to obtain an acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel; (c) adding nano nickel powder to the graphene oxide / carbon nanotube mixed solution and stirring evenly; then adding the acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel and mixing evenly to obtain graphene oxide / carbon nanotube-nano nickel composite ink; the mass ratio of the nano nickel powder, the graphene oxide / carbon nanotube mixed solution and the acrylic cross-linked resin / polyoxyethylene polypropylene triblock polymer mixed gel is 1500-2000:200-400:100-150; (d) loading the graphene oxide / carbon nanotube-nano-nickel composite ink into a 3D printer, setting the 3D printer parameters, and performing 3D printing on a glass sheet as a substrate to obtain a graphene oxide / carbon nanotube-nano-nickel composite hydrogel; (e) freeze-drying the graphene oxide / carbon nanotube-nano-nickel composite hydrogel to obtain a graphene oxide / carbon nanotube-nano-nickel composite aerogel; calcining the graphene oxide / carbon nanotube-nano-nickel composite aerogel at a high temperature under an inert gas to obtain a graphene oxide / carbon nanotube-nano-nickel electrode; the high-temperature calcination is performed in a tubular furnace at a temperature of 500-900° C. at a rate of 1-10° C. / min.
2. The method for preparing the graphene oxide / carbon nanotube-nano nickel electrode according to claim 1, characterized in that: Step (a) comprises: (a1) mixing graphene oxide and deionized water, and ultrasonicating and stirring to obtain a graphene oxide solution; (a2) mixing the carbon nanotubes with a mixed acid, stirring and reacting under heating conditions; then washing with deionized water and filtering to obtain a concentrated carbon nanotube solution, and calibrating its solid content; the mixed acid is a mixture of concentrated nitric acid and concentrated sulfuric acid; (a3) Ultrasonic mixing the graphene oxide solution and the concentrated carbon nanotube solution to obtain the graphene oxide / carbon nanotube mixed solution.
3. The method for preparing the graphene oxide / carbon nanotube-nano nickel electrode according to claim 2, characterized in that: The concentration of the graphene oxide solution is 10-30 mg / mL, the concentration of the concentrated carbon nanotube solution is 150-200 mg / mL, the feeding ratio of the carbon nanotubes, concentrated nitric acid and concentrated sulfuric acid is 1 g: 10-20 mL: 25-50 mL, and the feeding volume ratio of the graphene oxide solution to the concentrated carbon nanotube solution is 8-15:
1.
4. The method for preparing the graphene oxide / carbon nanotube-nano nickel electrode according to claim 1, characterized in that: Step (b) comprises: (b1) mixing an acrylic acid cross-linked resin and deionized water, and allowing the mixture to swell to obtain an acrylic acid cross-linked resin gel; (b2) mixing the polyoxyethylene polypropylene triblock polymer and deionized water, and allowing the mixture to swell to obtain a polyoxyethylene polypropylene triblock polymer gel; (b3) mixing the acrylic cross-linked resin gel and the polyoxyethylene-polypropylene triblock polymer gel to obtain an acrylic cross-linked resin / polyoxyethylene-polypropylene triblock polymer mixed gel.
5. The method for preparing the graphene oxide / carbon nanotube-nano nickel electrode according to claim 4, characterized in that: The concentration of the acrylic cross-linked resin is 15-25 mg / mL, the concentration of the polyoxyethylene polypropylene triblock polymer is 5-15 mg / mL, and the feeding volume ratio of the acrylic cross-linked resin gel to the polyoxyethylene polypropylene triblock polymer gel is 1:0.8-1.
2.
6. The method for preparing the graphene oxide / carbon nanotube-nano nickel electrode according to claim 1, characterized in that: In step (d), the graphene oxide / carbon nanotube-nano nickel composite ink is placed in a 3D printer syringe, and a printing needle compatible with the syringe is used; the diameter of the printing needle is 100-2000 μm, and the distance between the free end of the printing needle and the substrate is 0.70-0.8 times the diameter of the printing needle; the 3D printer parameters include: air pressure of 90-400 kPa, and a moving speed of the robotic arm of 1-30 mm / s.
7. A graphene oxide / carbon nanotube-nano nickel electrode, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 6.
8. The use of the graphene oxide / carbon nanotube-nano nickel electrode according to claim 7, characterized in that: Used for electrolysis of water under alkaline conditions.
Citation Information
Patent Citations
Preparation method of 3D-printing super porous elastic graphene aerogel
CN108046241A
Preparation method of carboxylic carbon nanotube / graphene aerogel / foam nickel composite electrode material
CN109449012A